Excellent low-temperature electrochemical cycling of an anode consisting of Si nanoparticles seeded in Sn nanowires for lithium-ion batteries. (10th November 2021) - Tian, Mengyu; Ben, Liubin; Jin, Zhou; Ji, Hongxiang; Yu, Hailong; Zhao, Wenwu; Huang, Xuejie
Abstract: Lithium-alloys such as metallic silicon (Si) and tin (Sn) with a high theoretical capacity are currently regarded as the most promising anode materials for the next generation of Lithium-ion batteries. Here, an anode consisting of Si nanoparticles (SiNPs) seeded in Sn nanowires (SnNWs) was synthesized via a facile solid-vapor reaction. Its electrochemical performance, particularly below room temperature (RT) was investigated in detail. The structured anode bestowed lithiation of SiNPs into the network of conducting SnNWs, resulting in significantly improved cycling performance, even at 0 and -20 °C. It demonstrated not only a high and stable capacity of ∼1500 mAh/g (0.2 C) at RT but also an excellent capacity of ∼1300 mAh/g at 0 °C and ∼600 mAh/g at −20 °C. The improved low-temperature cycling performance of the structured anode is attributed to its high lithium-ion chemical diffusion coefficient, low increase of charge transfer impedance, and high lithium intercalation kinetics.